Weak landscape-strong emission impact based development : is this the most likely response in all countries to global warming issues? - Muñoz, Lucio (Universidad Nacional de Quilmes, 2004)
One of the most politically sensitive development issues in all countries today is related to how to best proceed to comply with international agreements made to effectively and fairly address global warming issues. The objective of this paper is to show, using qualitative comparative means, that currently the most likely development scenario for developed and developing countries alike when facing global warming issues is one that is based on achieving weak landscape impacts and strong emission impacts at the same time as this type of program would reflect clearly the best economic interest of all of them and would allow them to display a more environmentally friendly attitude.